Penerapan Metode Interpolasi Lagrange Untuk Meramalkan Jumlah Pelanggan Listrik Bulanan di PT PLN Tasikmalaya - Santa Falare Sitanggang; Mikolis Etimanta Ginting; Valen Silvana Hasibuan; Agnes Miranda Sitanggang (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
Forecasting the number of electricity customers is a crucial aspect of resource planning and management at PT PLN Tasikmalaya. One method that can be used to improve forecasting accuracy is Lagrange Interpolation, which constructs an interpolation polynomial based on known data points. Although this method has been widely applied in various fields, its use in forecasting the number of electricity customers remains rare. Therefore, this study aims to explore the application of the Lagrange Interpolation method in forecasting the monthly number of electricity customers at PT PLN Tasikmalaya.In this study, historical electricity customer data was used as the basis for constructing an interpolation polynomial, which was then utilized to forecast the number of customers from January 2024 to May 2024. The forecasting results indicate an increase in the number of electricity customers each month. After rounding, the estimated number of customers is 274,952 in January 2024, 278,142 in February 2024, 284,402 in March 2024, 296,031 in April 2024, and 316,391 in May 2024.The findings of this study demonstrate that the Lagrange Interpolation method can be applied to forecast the monthly number of electricity customers at PT PLN Tasikmalaya. However, to improve forecasting accuracy, it is recommended to compare this method with other forecasting techniques and consider external factors that may influence the number of customers, such as government policies, economic growth, and changes in electricity consumption patterns.